Circulating tumour DNA is a potential biomarker for disease progression and response to targeted therapy in advanced thyroid cancer. (November 2018) - Allin, D.M.; Shaikh, R.; Carter, P.; Thway, K.; Sharabiani, M.T.A.; Gonzales-de-Castro, D.; O'Leary, B.; Garcia-Murillas, I.; Bhide, S.; Hubank, M.; Harrington, K.; Kim, D.; et al.
Abstract: Background: Conventional biomarkers in thyroid cancer are not disease specific and fluctuate in advanced disease, making interpretation difficult. Circulating tumour DNA (ctDNA) has been shown to be a useful biomarker in other solid tumours. This is a multimutational study of ctDNA over multiple timepoints, designed to test the hypothesis that ctDNA is a potential biomarker in patients with advanced thyroid cancer. Methods: Mutational analysis of archival tumour tissue was performed using NGS with a targeted gene panel. Custom TaqMan assays were designed for plasma ctDNA testing using digital droplet polymerase chain reaction. Concentrations of detected ctDNA were correlated with the conventional biomarker concentration and axial imaging status defined by the Response Evaluation Criteria in Solid Tumours criteria. Results: Tumour tissue from 51 patients was obtained, with the following histologies: 32 differentiated (differentiated thyroid cancer [DTC]), 15 medullary (medullary thyroid cancer [MTC]), three poorly differentiated and one anaplastic. NGS analysis detected variants in 42 (82%) of cases. Plasma was assayed for these patients in 190 samples, and ctDNA was detected in 67% of patients. Earlier detection of disease progression was noted in three patients with MTC. In two cases (PTC and ATC), where conventional biomarkers were not detectable, ctDNA was detected before disease progression. Changes in ctDNA concentration occurred earlier than conventional markers in response to disease progression in multiple patients with DTC receiving targeted therapies. Conclusion: The majority of patients with advanced thyroid cancer had detectable ctDNA. ctDNA measurement may offer superiority over conventional markers in several scenarios: earlier detection of progression in MTC; as an alternative biomarker when conventional markers are not available; more rapid assessment of the disease status in response to targeted therapies, thereby potentially allowing prompter discontinuation of futile therapies. These early results support the hypothesis that ctDNA may be a clinically useful biomarker in thyroid cancer. Highlights: Circulating tumour DNA (ctDNA) is found in majority (67%) of patients with thyroid cancer. Detection of ctDNA appears to be reflective of disease burden. ctDNA measurement may predict disease progression earlier than conventional biomarkers in medullary cancer. ctDNA measurement may allow more rapid assessment of response to targeted therapies in differentiated thyroid cancer.